Glacial and postglacial vegetation and climate history of the temperate ecosystem of Chilean central Patagonia (44º-49ºS) - (:unkn) unknown (My University, 2025)
The last decades have witnessed a significant increase in paleo-environmental studies concerning the vegetation and climatic history of central-western Patagonia (44º-49ºS) during and since the last glacial maximum (LGM). The contrasting interpretations of the terrestrial paleoecological records across the Andes in this region have led to divergent views on the direction/sign and chronology of paleoclimate events and vegetation colonization during and since the LGM, which pose an interesting biogeographical and paleoclimate puzzle. The validity and regional applicability of these stratigraphic, chronological and palynological interpretations, however, awaits replication with detailed stratigraphic from sensitive sites constrained by precise chronologies. We identify the series of unsolved problems in the paleoenvironmental evolution of central-west Patagonia: i) the chronology, structure and direction of climate changes (temperature and precipitation) at millennial timescales, ii) the behavior of the southern westerly winds (SWW) during and since the LGM, iii) the composition of the vegetation that thrived adjacent to the LGM margins, and iv) the tempo, mode and direction of the vegetation colonization through the increasingly icefree Patagonian landscapes during LGT. We address these problems through the following questions: How did the SWW vary (strength and/or latitudinal shifts) through from extreme glacial (22-18 ka) to extreme interglacial (11-8 ka) conditions? What was the regional climatic influence of the Patagonian Ice Sheet during last glacial termination in terrestrial environments? What were the possible dispersal routes of evergreen trees at regional scale through the increasingly ice-free Patagonian landscapes during last glacial termination? Determining the timing and direction of vegetation and paleoclimate changes in the southern mid-latitudes is a prerequisite for understanding the mechanisms involved in the generation and propagation of abrupt climate changes at hemispheric and global scales. In the southern mid-latitudes, the emphasis in the literature has been deciphering the role of the changes in latitudinal position and/or strength of Southern Westerly winds (SWW). To evaluate these problems, we propose to document the chronology, direction and rates of vegetation and climate changes based on pollen, sediment stratigraphy and C/N ratio, and fire history in records located in central Patagonia (~45°S). We propose develop paleoecological records from lake sediments from sites located in a transect west to east, which allow us to monitor and capture a range of changes in the precipitation in both sides of the Andes and pattern of vegetation colonization during and since the LGM. We will develop paleoecological records on lacustrine sediments obtained from medium size lake, simple batimetries and endorreic basins, which allow us to obtain multiple continuous records with high deposition rates. Thus, we can i) analyze in detail each basin indicating past changes in lake levels, which depend of the amount of precipitation, ii) apply the same methods to sample process, iii) develop high precision radiocarbon chronologies to establish comparisons between sites, iv) develop high resolution records and analyze the pattern of past vegetational changes, and v) develop high resolution macroscopic and microscopic charcoal records to reconstruct fire history in central Patagonia.